Ch. Delsol, J. Nowicki (éd.), La vie de l’esprit en Europe centrale et orientale depuis 1945. Dictionnaire encyclopédique, Les Éditions du Cerf, Paris 2021, pp. 1000. - Laurent Béghin (Studi Slavistici, 2022)
Book Review